Persistent Microalbuminuria in Human Immunodeficiency Virus Infected Children in Kano, Nigeria - Abdullahi Mudi; Bashir U. Alhaj; Fatimah Hassan-Hanga; Isah Adagiri Yahaya (International Journal of Nephrology)
Microalbuminuria has been reported to be a precursor of HIV related renal disease, which if detected early and coupled with appropriate intervention may slow or retard the progress of the disease. One hundred and seventy-eight HIV infected children aged 15 years and below were recruited from the Paediatric Infectious Disease Clinic of Aminu Kano Teaching Hospital (AKTH), Kano, to determine the prevalence of persistent microalbuminuria using the albumin creatinine ratio (ACR). Early morning urine samples and spot urine samples were analyzed using a dipstick specific for microalbumin. Those who tested positive had their samples reanalyzed in the laboratory using immunometric assay and Jaffe reaction method for albumin and creatinine, respectively. Patients that had ACR of 30–300 mg/g were said to have microalbuminuria and had their urine samples retested after 6 to 8 weeks. Twelve children (6.7%) had persistent microalbuminuria and had a mean age of 7.5±3.3 years, with a male to female ratio of 1 : 1. There was no significant relationship between the finding of microalbuminuria and age, sex, duration of infection, and the use of highly active antiretroviral therapy. Periodic screening for microalbuminuria using albumin specific dipstick should be considered for children with HIV infection.